High-density lipoprotein inhibits mechanical stress-induced cardiomyocyte autophagy and cardiac hypertrophy through angiotensin II type 1 receptor-mediated PI3K/Akt pathway - Lin, Li (J Cell Mol Med, 2015)
Mechanical stress triggers cardiac hypertrophy and autophagy through an angiotensin II (Ang II) type 1 (AT1) receptor-dependent mechanism. Low level of high density lipoprotein (HDL) is an independent risk factor for cardiac hypertrophy. This study was designed to evaluate the effect of HDL on mechanical stress-induced cardiac hypertrophy and autophagy. A 48-hr mechanical stretch and a 4-week transverse aortic constriction were employed to induce cardiomyocyte hypertrophy in vitro and in vivo, respectively, prior to the assessment of myocardial autophagy using LC3b-II and beclin-1. Our results indicated that HDL significantly reduced mechanical stretch-induced rise in autophagy as demonstrated by LC3b-II and beclin-1. In addition, mechanical stress up-regulated AT1 receptor expression in both cultured cardiomyocytes and in mouse hearts, whereas HDL significantly suppressed the AT1 receptor. Furthermore, the role of Akt phosphorylation in HDL-mediated action was assessed using MK-2206, a selective inhibitor for Akt phosphorylation. Our data further revealed that MK-2206 mitigated HDL-induced beneficial responses on cardiac remodelling and autophagy. Taken together, our data revealed that HDL inhibited mechanical stress-induced cardiac hypertrophy and autophagy through downregulation of AT1 receptor, and HDL ameliorated cardiac hypertrophy and autophagy via Akt-dependent mechanism.